Situation Report: Romania, 20 September 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania's Trade, East and West / by Paul Gafton Ceausescu Endorses the Succession Plan of Kim Il-Song / by Anneli Maier A Proposal on Euromissiles / by Vladimir Socor Chinese President Li Xiannian's Visit / by Anneli Maier Is Romanian Policy toward the Exiles Changing? / by Crisula Stefanescu Problems in Agriculture / by O. Rizzely Amnesty and Pardon Decree / by Paul Gafton Gheorghe Calciu, Defender of Religious Rights / by Vladimir Socor